2016
DOI: 10.1074/mcp.m115.053124
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Identification of Putative MicroRNA394 Target Genes in Arabidopsis thaliana Identifies Major Latex Protein Family Members Critical for Normal Development

Abstract: Expression of the F-Box protein Leaf Curling Responsiveness (LCR) is regulated by microRNA, miR394, and alterations to this interplay in Arabidopsis thaliana produce defects in leaf polarity and shoot apical meristem organization. Although the miR394-LCR node has been documented in Arabidopsis, the identification of proteins targeted by LCR F-box itself has proven problematic. Here, a proteomic analysis of shoot apices from plants with altered LCR levels identified a member of the Latex Protein (MLP) family ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 70 publications
1
23
0
Order By: Relevance
“…However, the molecular mechanisms underlying the metastasis-suppressive effects of miR-148a on NSCLC remain poorly understood. An increasing number of researchers employ proteomic strategies to seek downstream putative targets and molecular mechanisms modulated by miRNAs (16)(17)(18). In the present study, iTRAQ technology combined with NanoLC-MS/MS was used to analyze the global protein expression profiles of SPC-A-1 cells treated with the miR-148a inhibitor and control, and therefore, to explore the molecular mechanisms modulated by miR-148a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the molecular mechanisms underlying the metastasis-suppressive effects of miR-148a on NSCLC remain poorly understood. An increasing number of researchers employ proteomic strategies to seek downstream putative targets and molecular mechanisms modulated by miRNAs (16)(17)(18). In the present study, iTRAQ technology combined with NanoLC-MS/MS was used to analyze the global protein expression profiles of SPC-A-1 cells treated with the miR-148a inhibitor and control, and therefore, to explore the molecular mechanisms modulated by miR-148a.…”
Section: Discussionmentioning
confidence: 99%
“…Isobaric Tag for Relative and Absolute Quantitation (iTRAQ) labeling technology combined with nano liquid chromatography-mass spectrometry (NanoLC-MS/MS) has been employed effectively for biomarker discovery (15). As miRNAs not only induce alterations of the protein expression level of their target genes, but also indirectly change the expression of a range of proteins through interactions with target proteins, cancer research is turning to proteomics-based strategies to seek the putative targets and further molecular mechanisms modulated by miRNAs (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Among other interesting proteins, this proteomic analysis identified member of the Latex Protein family MLP423 as a potential target of LCR. Application of BiFC microscopic assay helped to prove the direct interaction of these two proteins, supporting that MLP is driven to degradation by LCR and this is important for normal SAM development [95].…”
Section: Microscopic Examination Of Protein-protein Interactions In Pmentioning
confidence: 98%
“…Shoot apical meristem (SAM) of Arabidopsis transgenic plants with either elevated or reduced levels of F-box protein called Leaf Curling Responsiveness (LCR) was subjected to shot gun proteomic analysis [95]. F-box proteins are components of SKP1-Cullin1-F-box E3 ubiquitin ligase complex, which catalyzes transfer of ubiquitin to the substrate protein.…”
Section: Microscopic Examination Of Protein-protein Interactions In Pmentioning
confidence: 99%
“…GhMLP28 acts as a positive regulator of GhERF6 and the two proteins might contribute to protection against Verticillium dahliae infection in cotton plants [32]. It was also reported that MLP was associated with vegetative to reproductive phase transition of meristem [33].…”
Section: Expression Analysis Of Erf and Interacting Protein Gene In Rmentioning
confidence: 99%